Nurses' knowledge towards clinical decision-making tools of peripheral intravenous catheter assessment - Daud, Azlina; Mohd Azmi, Fatin Najwa (Academic Inspired Network, 2024)
Abstract: Inadequate decision-making can contribute to a higher incidence of complications associated with peripheral intravenous catheters, such as infection, occlusion, dislodgement, and thrombosis. These complications not only harm patients but also contribute tothe financial burden on healthcare systems. Purpose: This study aimed to assess the knowledge of nurses towards clinical decision-making tools of peripheral intravenous catheters. Methodology: A cross-sectional study involved 75 nurses from the medical and surgical wards of a teaching hospital in the East Coast region. Nurses' knowledge was assessed using a self-administered questionnaire. Data were analysed with descriptive analysis. Result: The nurses' level of clinical decision-making of PIVC assessment tools was determined by the summation of the total score of the 19 questions. There are about 10 nurses (13%) who answered all the questions correctly. The statistical test shows that only 4% of nurses have a moderate level of knowledge score while about96% of nurses have a good level of knowledge score. Conclusion: This study showed that nurses know the clinical decision-making tools of peripheral intravenous catheter assessment. Regular educational programmes and audits would sustain the good nursing practice of peripheral intravenous catheter assessment.